2012
DOI: 10.1155/2012/236148
|View full text |Cite
|
Sign up to set email alerts
|

HCV-Related Nervous System Disorders

Abstract: Chronic infection with hepatitis C virus (HCV) is associated with a wide spectrum of extrahepatic manifestations, affecting different organ systems. Neurological complications occur in a large number of patients and range from peripheral neuropathy to cognitive impairment. Pathogenetic mechanisms responsible for nervous system dysfunction are mainly related to the upregulation of the host immune response with production of autoantibodies, immune complexes, and cryoglobulins. Alternative mechanisms include poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 79 publications
(75 reference statements)
0
91
0
4
Order By: Relevance
“…It is reported that chronic HCV infection has been associated with neurological as well as psychiatric conditions in upto about 50% of the cases [11] . Major HCV related neurological ailments comprise of autoimmune disorders, cerebrovascular events, myelitis, encephalopathy, encephalomyelitis, and cognitive impair ment; psychiatric disorders include, anxiety depression, and fatigue [12,13] . All the aforementioned complications that are manifested by HCV infection, regardless of the severity of disease [14] .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that chronic HCV infection has been associated with neurological as well as psychiatric conditions in upto about 50% of the cases [11] . Major HCV related neurological ailments comprise of autoimmune disorders, cerebrovascular events, myelitis, encephalopathy, encephalomyelitis, and cognitive impair ment; psychiatric disorders include, anxiety depression, and fatigue [12,13] . All the aforementioned complications that are manifested by HCV infection, regardless of the severity of disease [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Elôfordulása 14-50%. A vírus által kivál-tott inzulin rezisztencia a HCV cor protein közvetlen hatá-sa a hepatocytákban az inzulin szignál transzdukciós úton keresztül és a vírus replikáció által indukált, az endoplazmás retikulumra kifejtett stressz útján (18,(53)(54)(55) (56).…”
Section: Inzulin Rezisztencia 2-es Típusú Diabetes Mellitusunclassified
“…Central nervous system (CNS) involvement occurs in approximately 6% of cases. CGs are also a risk factor for carotid plaque formation, hepatic ibrosis, and liver steatosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of an immune-mediated process induced by HCV causes inlammatory disorders such as acute encephalitis, encephalomyelitis, and meningoradiculitis/polyradiculitis; there are reports of patients with rapidly evolving acute leukoencephalitis or fatal progressive acute encephalomyelitic syndromes [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation